2006
DOI: 10.1093/her/cyl052
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of implementation in a treatment effectiveness trial of Reconnecting Youth

Abstract: In 'a treatment effectiveness trial', a program is evaluated in a real-world setting, with an emphasis on achieving high implementation fidelity. Through fidelity assessment, the link between program implementation and outcomes is systematically evaluated and ultimately leads to a greater understanding of program success or failure. This paper reports the results of an implementation fidelity study of the 'Reconnecting Youth' (RY) prevention program. The research questions were (i) was the program implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 18 publications
1
65
0
4
Order By: Relevance
“…This advocacy for EBPs in substance abuse treatment is key to successful adoption and fidelity. 48,49 Indeed, a particularly important barrier to the implementation of EBPs are unsupportive state, local, and federal mental health authority administrative practices and policies. 15 The most prevalent examples are lack of a long-term vision, lack of agreement on desired outcomes, lack of penalties for non-evidenced-based practices, short-term horizons for policy planning, political mandates on competing public-sector priorities, resource limitations, and uncertainty associated with change and untoward events.…”
Section: Discussionmentioning
confidence: 99%
“…This advocacy for EBPs in substance abuse treatment is key to successful adoption and fidelity. 48,49 Indeed, a particularly important barrier to the implementation of EBPs are unsupportive state, local, and federal mental health authority administrative practices and policies. 15 The most prevalent examples are lack of a long-term vision, lack of agreement on desired outcomes, lack of penalties for non-evidenced-based practices, short-term horizons for policy planning, political mandates on competing public-sector priorities, resource limitations, and uncertainty associated with change and untoward events.…”
Section: Discussionmentioning
confidence: 99%
“…Mihalic et al (12) listed some barriers that have potential to affect the implementation quality, including failure to invest time and resources, hiring program implementers who lack the relevant skills to deliver the program, insuffi cient organizational and key leader support, poor motivation and buy-in of implementing staff, failure to provide continuing support and technical assistance, and lack of program monitoring. Sanchez et al (13) emphasized that incorporating the program into the school ' s formal curriculum with high program fi delity and a clear manpower deployment for program implementation is essential. Added to this, research studies indicated that the active involvement and support of school administrative personnel is another factor that enhances implementation success (14) .…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, consideramos que una de las fortalezas del estudio es el tamaño de muestra, con la participación de 39 escuelas, muestra muy superior a la de otros estudios 11,14,16,17,39,40 .…”
Section: Discussionunclassified
“…En los últimos años un elevado número de estudios han señalado la importancia de evaluar la fidelidad de la implementación de las inter venciones preventivas escolares [13][14][15][16][17][18] . Su evaluación nos puede conducir a un mejor entendimiento del éxito o fracaso de un programa ya que la obtención de los resultados esperados está estrechamente vinculada a la intensidad y cualidad de la implementación 15,19 .…”
Section: Introductionunclassified